The Digital Economy: Opportunities and Difficulties Islamic Economy's Future - Khalid, Muhammad Yasir; Abidin, Zaenal; Rochbani, Ita Tryas Nur (CV. Zabags Qu Publish, 2024)
The advent of technical innovation and economic digitalization via social media platforms and shopping applications has an impact on community social and economic activity. The manual, traditional economic system has been replaced by a modern one. A basic definition of a digital economy is any economic output that uses multifunctional internet-based technologies applied in a variety of digital business models for products or services. The expansion of the Islamic economy's involvement in e-commerce must be promoted in order to support the rise of financing via the digital economy and the empowerment that comes with it. One approach that can be used to create halal product innovations that are popular on the digital economy platform is principle-based regulation. With this technology, one would anticipate that. The results of this study demonstrate that initiatives to support innovation, entrepreneurship, and economic expansion may present a chance to increase access, particularly to Islamic economic inclusion. The digital economy is also anticipated to serve as a platform for the exchange of knowledge about how to better public services, finance, or social services, as well as new technologies that could offer all societal levels first-rate, quick, and reasonably priced Islamic economic services while also enhancing the effectiveness and efficiency of economic activity.